Collaborative Governance in the Development of Dayun Integrated Reservoir Tourism Objects in Siak Regency - Ulfika Affuri Toriqudin; Hasim As’ari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Dayun Embung Integrated Tourism is one of the artificial tours that has ASRI nuances (Safe, Healthy, Neat, and Beautiful). To develop into one of the leading destinations in Siak Regency, it cannot be separated from the problem of uniting conflicts of interest between parties involved in the collaboration process. The parties involved are the Tourism Office of Siak Regency, Dayun Village Government, Dayun Tourism Awareness Group, PT. Bumi Siak Pusako, and Delik.News.Com. This study aims to analyze collaborative governance in the development of tourism made by Embung Terpadu Dayun in Siak Regency and the inhibiting factors. The theory used is the collaborative governance process theory by Ansell and Gash, namely there are 5 processes: face to face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. The results of this study found that collaborative governance in the development of tourism made by the Dayun Integrated Embung was carried out face to face in the form of program meetings, then trust building with information disclosure and tourism confidence for the benefit of the community, then commitment to the synergy process to build the country with the concept of Sapta Pesona environment-based tourism, and shared understanding by implementing it jointly by building parts of them, as well as intermediate outcomes with the success of winning 1st place at the national level in the 2022 Indonesian Tourism Village Award Event. Another obstacle faced in this collaboration process is that communication in deliberation does not run effectively, the lack of a role from the Regency Tourism Office. Siak related to human resources, the absence of Mou, as well as the absence of retribution for tourist entrance tickets and parking.